Deficits in cognitive estimation in patients with right-frontal and right-temporal lobe epilepsy Neuropsychologische Schätzdefizite bei rechtsfrontaler und rechtstemporaler Epilepsie - Schwarz, Michael; Benkowitsch, Edith; Schneider, Katrin; Walther, Katrin; Hamer, Hajo (Zeitschrift für Neuropsychologie, 2021)
Background: Previous studies revealed a right-hemispheric dominance for cognitive estimation processes. Objectives: This study explored estimation impairments in patients with focal temporal and frontal lobe epilepsies. Methods: 109 patients (right frontal, left frontal, right temporal-mesial, right temporal-neocortical, left temporal-mesial, left temporal-neocortical) and a control group with 67 subjects were included. All subjects underwent an extensive neuropsychological assessment including the Test zum kognitiven Schätzen (TKS; Brand et al., 2002). Hypothesis: It was expected that right-hemispheric lesions would be associated with impairments in cognitive estimation. Results: Patients with right-frontal and right-temporal mesial focus showed significant estimation deficits compared to the other groups. Conclusion: This study shows that the right hemisphere dominantly participates in cognitive estimation.
CRIS-Team Scopus Importer:2021-06-11
Keywords: cognitive estimation; epilepsy; frontal lobe; hippocampus; laterality; temporal lobe